Pengembangan Lembar Kerja Siswa (LKS) Menggunakan Contextual Teaching and Learning (CTL) Berbasis Kota Lubuklinggau - Rani Refianti; Marisa Z Marisa Z; Novianti Mandasari (Jurnal Pendidikan Matematika:Judika Education, 2019)
The purpose of this study was to develop student worksheets (LKS) using the Lubuklinggau city-based Contextual Teaching and Learning (CTL) on the set material in class VII according to the 2013 curriculum and find out the quality of worksheets developed from the validity, practicality and potential effects of using LKS. The research method used is Research and Development (R&D) research. Development of worksheets using a 4-D model that was modified to a 3-D model. This model consists of 3 stages, namely: the stage of defining (Define), design (Development) and development (Develop) without including the spread (Disseminate) due to time constraints. The results of the study are based on the assessment analysis by the three experts namely: linguists, material experts, and media experts showing that the worksheet fulfills valid criteria with an average score of 3.12. While the results of the analysis of student response questionnaire assessments obtained that the student worksheets meet practical criteria with an average score of 3.55 and have a potential effect of 27 students (84.37%) whose grades reach mastery learning, while 5 students (15.63%) not reached mastery learning. In conclusion, the development of student worksheets using the contextual Teaching and Learning (CTL) based on the city of Lubuklinggau is declared valid, practical and has a potential effect on students' mastery learning. Keywords: Contextual Teaching and Learning, Student Worksheet